Indicators of Sovereign Risk of South Africa’s International Monetary Fund Loan: The Nexus Between Political Risks and Economic Growth - Mathebula, Ndzalama C. (Center for Risk Management & Sustainability and RSF Press, 2024)
Upon the approval of the 70 billion International Monetary Fund (IMF) loan for South Africa, concerns have emerged over the affordability of this loan and its impact on the economy and sovereignty of the country. South Africa’s ability to pay its IMF loan is assured because its track record of loan repayment is good, considering that the loan is repayable in five years at an interest rate of 1.1%. This study explores political and economic indicators of sovereign risk of South Africa’s IMF loan taken in 2020. The tenets of sovereign risk are being explored in a South African context. The significance of this study lies in understanding sovereign risk from a South African context and forecasting the country’s capacity and sustainability of servicing its IMF debt. This study presents a special and underexplored case of sovereign risk mainly due to 2020 being the first time South Africa has taken an IMF loan since the inception of a democracy in 1994. This qualitative study heavily relies on secondary literature, theories, and predictive forecasting models and is aided by descriptive statistics to reach its conclusion. Findings from the Council of Foreign Relations used the CFR Sovereign risk tracker designed to gauge the susceptibility of emerging economy to default on external debt.